The Concept of Ideal Protein in Formulation of Aquaculture Feeds - Richard D. Miles; Frank A. Chapman (EDIS)
FA-144, a 3-page fact sheet by Richard D. Miles and Frank A. Chapman, discusses the concept of using proteins meeting the digestible amino acids requirement of the fish using lysine as a reference, and the problem with using feed with an excess of protein. Published by the UF Department of Fisheries and Aquatic Sciences, March 2007.